THE PROPHETIC LAW, PANCASILA, AND INDONESIA’S SIGNIFICANT ROLE TOWARD INTERNATIONAL LAW IN ASIA-AFRICA, ASEAN, AND GLOBAL CONTEXT - Jawahir Thontowi; Erna Wati (RADJA PUBLIKA, 2023)
There is an interesting relation between Prophetic Law and Pancasila as well as Indonesian government significant role towards international law, both in theoretical and conceptual perspective. In Indonesian politic nowadays, the government have played significant role not only in observing international treaty but played a big role to the establishment of cooperation between non-block nations in Asia and Africa. On one hand, the perspective of theory and concept of Prophetic law is relevant. Prophetic law can be explained particularly through Prophetic leadership that is based on the holy book of various religion such as Judaism, Christianity, and Islam. On the other hand, however there is a significant relation between Prophetic Law and Pancasila when the founding fathers designed to formulate Pancasila as the state ideology of Indonesia. The founding fathers are nationalists and ulama. They are involved to discus and formulate to agree which ideology would be adopted in Indonesia once gaining its independence. Prophetic Law can be defined as rule of law are based on revelation by God through the Prophet. Fundamental principles of Prophetic Law are (1) God made Law; (2) liberty and humanity; (3) actual values. Prophetic Law doesn’t believe rule of law is just human rule of law, but rather to consider prophetic values. So, truth, justice, and values are not separated from the substantive of law. Prophetic Law is national identity.